A Review: The Styrene Metabolizing Cascade of Side-Chain Oxygenation as Biotechnological Basis to Gain Various Valuable Compounds - Oelschlägel, Michel; Zimmerling, Juliane; Tischler, Dirk (Frontiers in Microbiology, 2018)
Styrene is one of the most produced and processed chemicals worldwide and is released into the environment during widespread processing. But, it is also produced from plants and microorganisms. The natural occurrence of styrene led to several microbiological strategies to form and also to degrade styrene. One pathway designated as side-chain oxygenation has been reported as a specific route for the styrene degradation among microorganisms. It comprises the following enzymes: styrene monooxygenase (SMO; NADH-consuming and FAD-dependent, two-component system), styrene oxide isomerase (SOI; cofactor independent, membrane-bound protein) and phenylacetaldehyde dehydrogenase (PAD; NAD+-consuming) and allows an intrinsic cofactor regeneration. This specific way harbors a high potential for biotechnological use. Based on the enzymatic steps involved in this degradation route, important reactions can be realized from a large number of substrates which gain access to different interesting precursors for further applications. Furthermore, stereochemical transformations are possible, offering chiral products at high enantiomeric excess. This review provides an actual view on the microbiological styrene degradation followed by a detailed discussion on the enzymes of the side-chain oxygenation. Furthermore, the potential of the single enzyme reactions as well as the respective multi-step syntheses using the complete enzyme cascade are discussed in order to gain styrene oxides, phenylacetaldehydes, or phenylacetic acids (e.g., ibuprofen). Altered routes combining these putative biocatalysts with other enzymes are additionally described. Thus, the substrates spectrum can be enhanced and additional products as phenylethanols or phenylethylamines are reachable. Finally, additional enzymes with similar activities toward styrene and its metabolic intermediates are shown in order to modify the cascade described above or to use these enzyme independently for biotechnological application.